The Value of Anlotinib in the Treatment of Intractable Brain Edema: Two Case Reports - Yang, Song; Sun, Jian; Xu, Mingna; Wang, Yuru; Liu, Guihong; Jiang, Aijun (Frontiers in Oncology, 2021)
About 20-30 percent of patients with cancer, such as non-small cell lung cancer, breast cancer, melanoma and renal cell carcinoma, will develop brain metastases (BM). Primary and secondary brain tumors are often accompanied by peritumoral edema. Due to the limited intracranial space, peritumoral edema will further increase the intracranial pressure and aggravate clinical symptoms. Radiotherapy, as a basic component of the treatment of intracranial tumors, induces blood vessel damage and aggravates brain edema. The combination of edema caused by the tumor itself and radiotherapy is collectively referred to as intractable brain edema. Edema can increase intracranial pressure and cause associated neurologic symptoms, which seriously affects the quality of life of patients. Steroids, specifically dexamethasone, have become the gold standard for the management of tumor-associated edema. However, steroids can lead to variety of adverse effects, including moon face, high blood pressure, high blood sugar, increased risk of infection, bone thinning (osteoporosis), and fractures, especially with prolonged use. The investigation of other types of drugs is urgently needed to address this problem.Compared to other anti-angiogenic agents, anlotinib acts on vascular endothelial growth factor receptors (VEGFR1, VEGFR2/KDR, and VEGFR3), fibroblast growth factor receptors (FGFR1, FGFR2, FGFR3 and FGFR4), platelet derived growth factor receptor (PDGFR) and stem cell factor receptor (c-kit) simultaneously. However, according to the literature retrieval, there are no studies on anlotinib for the treatment of intractable brain edema. We describe here two cases of brain edema and review the literature available and hope to discover new agents that are safer and more effective.